FACTORS AFFECTING STRATEGY IMPLEMENTATION IN SOCIAL SECURITY INSTITUTIONS: A CASE STUDY OF NSSF - GACHERU, CAROLINE WANJIRU; Muchemi, M/S Anne (Journal of Public Policy and Administration, 2016)
Purpose: The current study is an assessment of the factors affecting strategy implementation in social security institutions. A case study of NSSF was taken Methodology: The study adopted a descriptive case study research design. The population of the study was 1660 employees of NSSF. Sampling targeted 10.4 percent of the total population of employees. Stratified random sampling was used to select the 173 employees from three strata namely, top management, middle management and junior officers. The study adopted a descriptive case study research design. Data was analyzed by the use of descriptive statistics and inferential analysis. Specifically, means, frequencies and percentages were used. Factor Analysis and Correlation analysis was used to extract the relevant factors and their relationship with strategy implementation. The findings presented in tables, figures and graphs. Results: Findings indicated that the organization leadership at NSSF is not effective and this may have led to poor strategy implementation. The culture at NSSF was not conducive for strategy implementation and this may have led to poor strategy implementation. The organization structure at NSSF was inconsistent with strategy implementation and this may have led to poor strategy implementation. The management of organization resources at NSSF is not effective and this may have led to poor strategy implementation. The organization politics at NSSF are not conducive for strategy implementation and this may have contributed to the poor implementation of strategy. Unique contribution to theory, practice and policy: The study suggests that the study should be replicated in the private sector institutions that deal with retirement savings. This would yield results for comparison between private and public institutions. In addition, this study is merely descriptive and lacks statistical rigor. It is therefore suggested that regression and correlation analysis should be conducted in future studies in order to establish the sensitivity of the factors to strategy implementation.